Adding Polymer to Mortar Mixture According to the Procedure Recommended by ASTM C 1439 - Kammouna, Zainab M. I. (Nahrain University College of Engineering Journal, 2011)
Polymers are considered one of the admixture kinds which they are used to improve the qualit and the performance of mortar and concrete. I this study the Styrene Butadiene Rubber (SBR) was used as a polymer to see its effects on the mortar. The (SBR) is considered as a water resistance polymer and bonding agent. Four cement mortar mixes were made in this study, the first one was considered as a reference mix which is not include (SBR) while the other mixes were included (SBR) in deferent percentages. The (SBR) was added as a percentage of cement weight. The amount of mixing water was varied to achieve the same flow which was accomplished in the reference mix throughout carrying out flow table test. Flow table test was adopted according to ASTM C 1439-99 (1) recommendations. For each mix, two prisms were prepared to carry out the drying shrinkage test, nine cubes for the compressive strength test and three cubes for the total water absorption test. It was found that when the quantity of (SBR) increases, the physical properties of mortar under study (drying shrinkage, compressive strength and total water absorption) deteriorate which is adverse to the proposal of advantages due to adding (SBR). This result leads to that the recommendation of ASTM C 1439-99 (1) that adopt the flow table as criteria of adjusting the amount of adding water accompanying with deferent percentages of (SBR) is not adequate.